Indicadores de desarrollo sostenible para la poblacion circundante de Puerto Masusa generado por las empresas madereras, Iquitos, Perú, 2022 - Isuiza Vidaurre, Samantha Vinori (2024)
The present study was carried out in the population, surrounding logging companies of Puerto Masusa, Punchana dictrict; with the purpose of evaluating the sustainable developent indicators for the surrounding population of Puerto Masusa generated by logging companies. From the obtained results, the Sustainable Development variable, such as wood Industries, obtained 0.73 and 0.70 Cronbach coefficient, which places the Sustainable Development variable in the category of excelllent reliability and in the case of the Industries variable Lumber companies in the very reliable category. Sustainable development and its impact in the surrounding population is only good in 27% and fair in 42%. In the social aspect of the Sustainable Development variable, the company Corecom SAC achieved the best performance among all the companies studied with 28 favorable responses in the Always area. The variable Sustainable Development, the Environmental Aspect presented the best performance with 25 responses obtained with the response ALWAYS qualifying as good from a total of 75 workers. The variable wood Industries in Ecological Management presented the best performance with 27 responses obtained with the response ALWAYS qualifying as good from a total of 36 workers. The Ch² test shows that the alternative Hypothesis is approved and the null hypothesis is rejected.